2019
DOI: 10.3390/min9110714
|View full text |Cite
|
Sign up to set email alerts
|

Grinding Kinetics of Slag and Effect of Final Particle Size on the Compressive Strength of Alkali Activated Materials

Abstract: This study aims to model grinding of a Polish ferronickel slag and evaluate the particle size distributions (PSDs) of the products obtained after different grinding times. Then, selected products were alkali activated in order to investigate the effect of particle size on the compressive strength of the produced alkali activated materials (AAMs). Other parameters affecting alkali activation, i.e., temperature, curing, and ageing time were also examined. Among the different mathematical models used to simulate … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 67 publications
(90 reference statements)
2
11
0
Order By: Relevance
“…As can be seen in Table 3, which shows the calculated parameters K and M by fitting the Alyavdin equation to experimental data, the grinding rate constant K decreases from 0.206 to 0.043 when f c increases from 5% to 15%. It is also seen that M values range between 0.780 and 1.084, confirming the non-first-order grinding behavior of the ore [37,41,54]. Figure 4b) shows the presence of anatase that occurs in the form of individual microscale particles (<2 μm) widely dispersed within the diasporic core (center of the clast) as well as in the form of intergrown particles within the internal rings of hematite (inner-outer dashed line area) in the diasporic clast [11].…”
Section: Kinetic Behavior Of Grinding Processsupporting
confidence: 61%
See 2 more Smart Citations
“…As can be seen in Table 3, which shows the calculated parameters K and M by fitting the Alyavdin equation to experimental data, the grinding rate constant K decreases from 0.206 to 0.043 when f c increases from 5% to 15%. It is also seen that M values range between 0.780 and 1.084, confirming the non-first-order grinding behavior of the ore [37,41,54]. Figure 4b) shows the presence of anatase that occurs in the form of individual microscale particles (<2 μm) widely dispersed within the diasporic core (center of the clast) as well as in the form of intergrown particles within the internal rings of hematite (inner-outer dashed line area) in the diasporic clast [11].…”
Section: Kinetic Behavior Of Grinding Processsupporting
confidence: 61%
“…As can be seen in Table 3, which shows the calculated parameters K and M by fitting the Alyavdin equation to experimental data, the grinding rate constant K decreases from 0.206 to 0.043 when fc increases from 5% to 15%. It is also seen that M values range between 0.780 and 1.084, confirming the non-first-order grinding behavior of the ore [37,41,54].…”
Section: Kinetic Behavior Of Grinding Processsupporting
confidence: 60%
See 1 more Smart Citation
“…Petrakis et al [10] evaluated the particle size distribution (PSD) of crushed Ferro-nickel slag at different residence time. Then, selected products were alkali activated in order to investigate the effect of particle size on the compressive strength of the produced alkali activated materials (AAMs).…”
Section: Introductionmentioning
confidence: 99%
“…Also, many mechanical activation methods may affect the size reduction of coal fly ash particles. It has been reported that the reduction of particle size improved the rate of geopolymerization reactions [21,22]. It has also been reported that the strength of the geopolymer was improved by applying the high activity of the nanoparticles [23,24].…”
Section: Introductionmentioning
confidence: 97%